2019
DOI: 10.1590/s0004-2803.201900000-54
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Risk Scores in Variceal Bleeding

Abstract: BACKGROUND: Variceal bleeding remains important cause of upper gastrointestinal bleed. Various risk scores are used in risk stratification for non-variceal bleed. Their utility in variceal bleeding patients is not clear. This study aims to compare probability of these scores in predicting various outcomes in same population. OBJECTIVE: This study aims to compare probability of these scores in predicting various outcomes in same population. To study characteristics and validate AIMS65, Rockall, Glasgow Blatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
5
1
2
Order By: Relevance
“…One study used the AIMS65, MELD, APACHE II, and Child-Pugh scores to predict mortality in cases of acute variceal hemorrhage in cirrhotic patients and showed that the AIMS65 score had the highest sensitivity and specificity [25]. A different study reported that the AIMS65 and Rockall scores were superior to the other assessed scoring systems in predicting mortality [26]. In our study, the AIMS65 and Rockall scoring systems were less reliable compared to other scoring systems.…”
Section: Resultscontrasting
confidence: 61%
“…One study used the AIMS65, MELD, APACHE II, and Child-Pugh scores to predict mortality in cases of acute variceal hemorrhage in cirrhotic patients and showed that the AIMS65 score had the highest sensitivity and specificity [25]. A different study reported that the AIMS65 and Rockall scores were superior to the other assessed scoring systems in predicting mortality [26]. In our study, the AIMS65 and Rockall scoring systems were less reliable compared to other scoring systems.…”
Section: Resultscontrasting
confidence: 61%
“…Eleven out of 28 studies were prospective. Nine studies reported sensitivity and specificity values [ 19 , 21 , 26 , 27 , 32 , 34 , 36 , 38 , 42 ]. All studies presented AUCs and 95% CIs.…”
Section: Resultsmentioning
confidence: 99%
“…Another study compared the risk of clinical adverse events using the GBS and RS scores in NVUGIB and VUGIB patients, demonstrating that GBS can only predicted rebleeding risk in the NVUGIB subgroup and had lower predictive ability for rebleeding risk in VUGIB patients [16]. A prospective study in Brazil analyzed the ability of RS, GBS, AIMS65 and PNED (Progetto Nazionale Emorragia Digestiva) to predict rebleeding risk in VUGIB patients, revealing that only RS and PNED could predict rebleeding risk within 30 days, but both had AUC values below 0.7 (0.662 vs. 0.652, respectively) [17]. These research ndings indicate that although these scoring systems exhibit some accuracy in predicting rebleeding risk in NVUGIB patients, none of them can accurately predict rebleeding risk in VUGIB patients.…”
Section: Discussionmentioning
confidence: 99%